2011
DOI: 10.1143/jjap.50.06gm05
|View full text |Cite
|
Sign up to set email alerts
|

Microjoining of LSI Chips on Poly(ethylene naphthalate) Using Compliant Bump

Abstract: We show that microjoining of LSI chips on a film made of poly(ethylene naphthalate) (PEN), whose glass transition temperature is 155 °C, can be realized by using a cone-shaped compliant bump for flexible electronics. A 20-µm-pitch area array of cone-shaped Au bumps was fabricated on a Si wafer by photolithography and electroplating. The counter electrode on the PEN film was composed of a Au (top)/Ni/Al (bottom) layered structure, where Ni and Au layers were deposited by electroless plating on patterned Al. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The resistance for a bump connection is evaluated to be 83.4 m from the slope of the plot. This value is almost the same value as the resistance obtained from thermo-compression bonding at 150 C. 16) When flat-top bumps were used instead of the cone bumps, number of connected bumps decreased and resistance increased because of generation of bonding failure as shown in Fig. 5(d).…”
Section: Electrical Connection Testsupporting
confidence: 64%
See 2 more Smart Citations
“…The resistance for a bump connection is evaluated to be 83.4 m from the slope of the plot. This value is almost the same value as the resistance obtained from thermo-compression bonding at 150 C. 16) When flat-top bumps were used instead of the cone bumps, number of connected bumps decreased and resistance increased because of generation of bonding failure as shown in Fig. 5(d).…”
Section: Electrical Connection Testsupporting
confidence: 64%
“…[18][19][20] In the previous work, solid phase bonding of Au-Au was achieved even at 150 C owing to its mechanical compliance. 16) In addition, we have shown that combination of the cone bump and a counter electrode with a crossshaped slit enables the bonding of LSI chips to circuits on a plastic film at room temperature. 17) However, the formation of the slit in the counter electrode requires additional photolithography process which increases the fabrication cost.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…When we analyzed the deformation of the PEN film during bonding by using the finite element method (FEM), the deformation of the PEN film under the Au/Ni/Al electrode was only 0.15 m under the application of 1.0 gf/bump. 17) From the simulation, we also found that the deformation of the PEN film is 0.08 and 0.12 m under the application of 0.5 and 0.75 gf/bump, respectively. Since the cross-shaped slit is not formed in the simulation and the thickness of the Ni obtained by the experiment is about 2 m smaller than that in the simulation, the deformation of the PEN film might be slightly larger than the simulation results under the application of a pressing load.…”
Section: Resultsmentioning
confidence: 64%
“…Recently, we have shown that the use of cone-shaped compliant bumps 15,16) enables the bonding of a Si chip to metal electrodes on a PEN film at 150 C. 17) However, 150 C is close to the glass transition temperature of PEN, 155 C, and therefore softening of the PEN film surface may take place as was suggested by the experimental results described in a previous report. 17) Therefore, further decrease in bonding temperature is required. Our target is bonding at room temperature.…”
Section: Introductionmentioning
confidence: 99%